2020
DOI: 10.3390/ma13194302
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Oxycarbide-Graphite Electrodes for High-Power Energy Storage Devices

Abstract: Herein we present a study on polymer-derived silicon oxycarbide (SiOC)/graphite composites for a potential application as an electrode in high power energy storage devices, such as Lithium-Ion Capacitor (LIC). The composites were processed using high power ultrasound-assisted sol-gel synthesis followed by pyrolysis. The intensive sonication enhances gelation and drying process, improving the homogenous distribution of the graphitic flakes in the preceramic blends. The physicochemical investigation of SiOC/grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…It is a result of kinetics and thermodynamic limitations of the diffusion of Li ions at the surface of electrode and electrolyte. In contrary to these findings, Fukui et al [448,449], Graczyk-Zajac et al [450,451], Dibandjo et al [52], Knozowski et al [436,452], Kaspar et al [453,454], Wilamowska et al [455], and Pradeep et al [456,457] demonstrated that the carbon phase is the major Li-ion storage host site. It has been shown that lithium is accommodated in interstitial and defect sites, edges of graphene sheets, and adsorbed on the interface of graphite nano-crystallites.…”
Section: Anode Materials In Lithium-ion Batteriesmentioning
confidence: 92%
See 1 more Smart Citation
“…It is a result of kinetics and thermodynamic limitations of the diffusion of Li ions at the surface of electrode and electrolyte. In contrary to these findings, Fukui et al [448,449], Graczyk-Zajac et al [450,451], Dibandjo et al [52], Knozowski et al [436,452], Kaspar et al [453,454], Wilamowska et al [455], and Pradeep et al [456,457] demonstrated that the carbon phase is the major Li-ion storage host site. It has been shown that lithium is accommodated in interstitial and defect sites, edges of graphene sheets, and adsorbed on the interface of graphite nano-crystallites.…”
Section: Anode Materials In Lithium-ion Batteriesmentioning
confidence: 92%
“…All these benefits make PDCs promising candidates for anodes in LIBs. Besides, all above properties including porosity can be easily adjusted by chemical modification of the preceramic polymer and by tunable parameters during the polymer-to-ceramic transformation [179,[434][435][436].…”
Section: Anode Materials In Lithium-ion Batteriesmentioning
confidence: 99%
“…As both the free-carbon content and its type can vary, silicon-oxycarbide-based black glass can be a semiconductor or insulator, and the addition of carbon forms, for example, can make the material conductive [6]. Such properties make silicon oxycarbide a promising material for protective coatings [7,8], electrodes in batteries [9], fuel cells [10], catalysis [11,12], or in medicine [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Materials 2021, 14, x FOR PEER REVIEW 2 of 17 protective coatings [7,8], electrodes in batteries [9], fuel cells [10], catalysis [11,12], or in medicine [13,14]. The synthesis of silicon-oxycarbide-based black glass is impossible with standard powder methods.…”
Section: Introductionmentioning
confidence: 99%
“…The most direct one is the possibility of enhancing material strength, as it was reported that even an addition of 1 wt.% of CNTs can increase it in other materials by up to five times [20]. The other reason to include carbon phases in general is enhanced conductivity, as it turns mostly non-conductive silicon oxycarbide into a conductor [21], which could increase its usefulness in electric devices such as batteries [22] or fuel cells [23]. As all these properties are highly dependent on CNTs' dispersion in the material, it is of utmost importance to prevent CNTs' aggregation [24].…”
Section: Introductionmentioning
confidence: 99%